SYSTEMATIC LITERATURE REVIEW: THE IMPACT OF SOCIAL COMPETENCE ON TEACHER COMMUNICATION INTELLIGENCE - Rasdiany, Apriana Nofriastuti; Akmal, Fauzi; Pasaleron, Roni; Dafrizal, Dafrizal; Ningsih, Rahayu; Rahman, Ikhwan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Social competence is an aspect that must be possessed by professional teachers. Social competence will form an intelligent teacher in establishing relationships and communication with the school environment such as students, teachers, parents and the community. This article aims to analyze the impact of teachers' social competence on communication intelligence so that they become professional teachers. This article uses the Systematic Literature Review method. Data sources were taken from forty selected scientific articles of high reputation which have been published in the Google Scholar, Scopus, DOAJ, ScienceDirect, Taylor & Francis databases, the articles in question were published in the 2019-2024 time period. All articles were analyzed using VOSViewer software by generating themes related to the issues studied such as social competence, Islamic religious education teachers, social intelligence. Data analysis found three impacts of teacher social competence on teacher communication intelligence; i) increasing time to communicate with students, ii) always collaborating on performance with the teacher council, iii) establishing communication with the community outside the school such as parents and partner schools. The description of the three findings ofthis analysis can be a reference for teachers as professional educators to always do the best with their environment, both for school residents and community members outside the school.